Hyperglycaemic preterm neonates exhibit insulin resistance and low insulin production. Issue 1 (5th September 2017) - Salis, Emma R; Reith, David M; Wheeler, Benjamin J; Broadbent, Roland S; Medlicott, Natalie J
Abstract : Objectives: To explore and compare the relationships between postmenstrual age (PMA), insulin, C-peptide and blood glucose concentrations (BGC) in hyperglycaemic and euglycaemic preterm neonates (PMA <30 weeks). Design: Observational. Setting: Dunedin Hospital Neonatal Intensive Care Unit, New Zealand. Patients: Preterm neonates were recruited and included nine insulin-treated hyperglycaemic and 20 euglycaemic neonates. Samples for euglycaemic neonates were obtained from leftover blood, and for insulin-treated neonates, additional blood was collected at the same time as the patients' routine 4 hourly blood glucose test over a 24-hour period (six samples). Main outcome measures: Blood samples were collected, plasma was analysed for insulin and C-peptide and was measured in temporal association with BGC. Results: The euglycaemic neonates had a mean PMA (SD) of 28 (1.4) weeks and the insulin-treated neonates had 25.5 (1.8) weeks. C-peptide plasma concentrations were significantly lower (p<0.01) in the insulin-treated hyperglycaemic neonates (51.7 (100) pmol/L; 200(208) pmol/L) indicating lower insulin production. Insulin plasma concentrations (r=−0.38), BGC (r=−0.38), C-peptide plasma concentrations (r=0.36) and insulin/C-peptide ratios (r=−0.49) were all significantly affected by PMA (p<0.01). As expected, insulin plasma concentrations were higher in the insulin-treated hyperglycaemic neonates (156 (161) pmol/L; 93.2 (63.1) pmol/L, p<0.01) confirming that intravenous exogenous insulin reached these neonates. Conclusions: This study demonstrates that preterm neonates exhibit insulin resistance, hyperglycaemic neonates have lower insulin production than euglycaemic neonates and treatment with exogenous insulin did not appear to suppress insulin production in these neonates.